Factors associated with preferred place of death among older adults: a qualitative interview study in Tama City, Tokyo, Japan. Issue 5 (24th May 2022) - Tsuchida, Tomoya; Onishi, Hitotaka; Ono, Yoshifumi; Machino, Aco; Inoue, Fumiko; Kamegai, Manabu
Abstract : Objectives: To analyse the cognitive processes involved in the decision-making of older adults who are not in the end-of-life stage regarding the selection of a preferred place of death. Design: A qualitative cross-sectional study based on semistructured in-depth interviews. The interview scripts were sectioned by context, then summarised, conceptualised and categorised. Post-categorisation, the relationships between the conceptual factors were examined. Setting: Tama City, Tokyo, Japan, from November 2015 to March 2016. Participants: 20 long-term care users and their families or care providers were interviewed about their preferred places of death and the factors behind their decisions. Results: Three categories based on the preferred place of end-of-life care and death were extracted from the interview transcripts: (A) discouraging the decision of a preferred place of death, (B) enhancing the desire for home death and (C) enhancing the desire for a hospital/long-term care facility death. Category A consists of concerns about the caregiver's health, anxiety about solitary death, and constraints of and concerns about the household budget. Both categories B and C consist of subcategories of reinforcing and inhibiting factors of whether to desire a home death or a hospital/long-term care facility death. If their previous experiences with care at home, a hospital or a care facility were positive, they preferred the death in the same setting. If those experiences were negative, they tend to avoid the death in the same setting. Conclusions: One's mindset and decision regarding a preferred place of death include the consideration of economic factors, concerns for caregivers, and experiences of care at home or in a hospital/long-term care facility. Furthermore, health professionals need to be aware of the ambivalence of senior citizens to support their end-of-life decisions.